Students' reading comprehension performance with emotional literacy-based strategy intervention - Mohd Yussof, Yusfarina; Jamian, Abdul Rasid; Zainon Hamzah, Zaitul Azma; Roslan, Samsilah (Australian International Academic Centre, 2013)
An effective reading comprehension process demands a strategy to enhance the cognitive ability to digest text information in the effort to elicit meaning contextually. In addition, the role of emotions also influences the efficacy of this process, especially in narrative text comprehension. This quasi-experimental study aims to observe students’ performance in the Reading Comprehension Test resulting from Emotional Literacy-Based Reading Comprehension Strategy (ELBRCS), which is a combination of cognitive and affective strategies. This study involved 90 students, whereby 45 students were clustered in the Experimental Group and received the ELBRCS intervension. The remaining 45 students were placed in the Control Group and underwent the conventional strategy (prevalent classroom method).The students’ reading comprehension performance was measured using the Reading Comprehension Test (RCT). The findings show that the experimental group received a higher score than the control group for RCT. The intervention has successfully increased student’s Reading Comprehension from literal comprehension to higher levels of comprehension i.e. inferential, evaluative and appreciative levels, as indicated by Barret’s Taxonomy.